Asymmetric Dimethylarginine at Sea Level Is a Predictive Marker of Hypoxic Pulmonary Arterial Hypertension at High Altitude - Siques, Patricia; Brito, Julio; Schwedhelm, Edzard; Pena, Eduardo; León-Velarde, Fabiola; De La Cruz, Juan José; Böger, Rainer H.; Hannemann, Juliane (Frontiers in Physiology, 2019)
Background: Prolonged exposure to altitude-associated chronic hypoxia (CH) may cause high altitude pulmonary hypertension (HAPH). Chronic intermittent hypobaric hypoxia (CIH) occurs in individuals who commute between sea level and high altitude. CIH is associated with repetitive acute hypoxic acclimatization and conveys the long-term risk of HAPH. As nitric oxide (NO) regulates pulmonary vascular tone and asymmetric dimethylarginine (ADMA) is an endogenous inhibitor of NO synthesis, we investigated whether ADMA concentration at sea level predicts HAPH among Chilean frontiers personnel exposed to six months of CIH. Methods: In this prospective study, 123 healthy army draftees were subjected to CIH (5 days at 3,550 m, 2 days at sea level) for six months. In 100 study participants with complete data, ADMA, symmetric dimethylarginine (SDMA), L-arginine, arterial oxygen saturation (SaO2), systemic blood pressure, and hematocrit were assessed at months 0 (sea level), 1, 4, and 6. Acclimatization to altitude was determined using the Lake Louise Score (LLS) and the presence of acute mountain sickness (AMS). Echocardiography was performed after six months of CIH in 43 individuals with either good (n=23) or poor (n=20) acclimatization. Results: SaO2 acutely decreased at altitude and plateaued at 90% thereafter. ADMA increased and SDMA decreased during the study course. The incidence of AMS and the LLS were high after the first ascent (53 and 3.1±2.4) and at one month of CIH (47 and 3.0±2.6), but decreased to 20 and 1.4±2.0 at month 6 (both p<0.001). 18 participants (42%) showed a mean pulmonary arterial pressure (mPAP) >25 mm Hg, out of which 9 (21%) were classified as HAPH (mPAP≥30 mm Hg). ADMA at sea level was significantly associated with mPAP at high altitude in month 6 (R=0.413; p=0.007). In ROC analysis, a cut-off for baseline ADMA of 0.665µmol/l was determined to predict HAPH (mPAP>30 mm Hg) with a sensitivity of 100% and a specificity of 63.6%. Conclusions: ADMA concentration increases during CIH. ADMA at sea level is an independent predictive biomarker of HAPH. SDMA concentration decreases during CIH and shows no association with HAPH. Our data support a role of impaired NO-mediated pulmonary vasodilation in the pathogenesis of HAPH.